THE USE OF TIKTOK DUET CONVERSATION TO IMPROVE STUDENTS’ SPEAKING SKILL AT SMK KRISTEN IMANUEL LAIKIT - Bunga, Joshua Christian; Liando, Nihta V. F.; Kumayas, Tirza A. (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2024)
The purpose of this study was to find out whether the use of Tiktok Duet Conversation can improve the speaking skill of tenth grade students at SMK Kristen Imanuel Laikit. The writer used quantitative methods to collect data, with pre-experimental designs and using one pre-test and post-test group. 21 grade X students of SMK Kristen Imanuel Laikit as samples in the study. The results of this study are obtained from before and after treatment. While the analysis data used t-test and then the results of the pre-test and post-test were analyzed using SPSS 24. The results of the study obtained showed differences in students’ speaking scores on the pre-test and post-test. It can be seen from the sig value of the 2-tailed paired sample test is 0.000 < 0.05, which means that Ha is accepted and Ho is rejected. It was concluded that using TikTok Duet Conversation has a very relevant influence on improving the speaking skill of tenth grade students of SMK Kristen Imanuel Laikit.